O curso de especialização em gênero e diversidade na escola (GDE) : uma perspectiva emancipadora pela igualdade de diferenças - Santana, Amanda de Oliveira (2020)
This study has as main objective to understand the impacts of the continued formation of graduates of the specialization course in Gender and Diversity in School (GDS) who nowadays act as teachers in the public and private network of basic education in the interior of the state of Mato Grosso. The dialogue in the form of an in-depth interview took place from the theoretical-methodological guidelines of communicative research and is theoretically based on the Theory of Communicative Action, by Habermas, and also on the concept of Dialogicity, by Freire. In them, there are essential elements for the understanding of social phenomena starting from the horizontal interaction and the egalitarian dialogue between the subjects. The interviews were conducted with two participants, a cisgender man and a cisgender woman, both teachers from the public school system, and took place in three phases: initial meeting to present and bond, second meeting to deepen the key questions, and finally, reading the synthesis. In this methodological perspective, the researcher synthesizes the information collected, however, after analysis, the interpreted information must return to the participant. Such feedback is important to ensure that the language is focused on understanding, establishing a greater understanding of what was said by the participant. This process is important for the construction of an egalitarian dialogue, breaking with the hierarchy between researcher and participant. In this sense, the central concept adopted is unity in diversity, versed in the Freirean perspective of the term, understanding that all people have the right to have an egalitarian education, through diversity, in a perspective of equality - the equality of differences. About data analysis, such organization is carried out through two dimensions: exclusive and transforming.